Home Along Da Riles a redevelopment of the Sta.Mesa PNR Station - Alvarez, Arvic G. (College of Architecture, University of the Philippines Diliman, 2020)
There are thousands of households that live along the tracks of the Philippine National Railways. Unfortunately, these informal settlers are believed to be hindrances to the development of the transit line. Despite the vibrancy that these communities contribute, they are rarely considered in PNR's redevelopment plans. The research challenges the common perception that the PNR and the communities cannot coexist side by side. To achieve the goals of the research, it is important to have a comprehensive understanding of the needs and potential of both stakeholders. This project explores the possibility of introducing a mutualistic relationship where both housing and transport components are integrated seamlessly under one facility.